PERAN GURU DALAM MEMBENTUK KARAKTER SISWA MELALUI PEMBELAJARAN NILAI-NILAI KEAGAMAAN - Annisa Raudatul Jannah; Najwa Aulia Putri; Desty Endrawati Subroto (Jurnal Padamu Negeri, 2025)
In this modern era, advances in technology and social media play a big role in shaping children's character. Easy access to information and social interaction through social media can have a positive or negative impact on student character development. As an effort to overcome these negative impacts, Islamic religious education in schools plays an important role in forming characters with noble character. This research aims to analyze the role of Islamic Religious Education Teachers in shaping student character through religious values ​​at the MTS 1 Pandeglang school. Islamic Religious Education Teachers are not only tasked with delivering religious material, but also function as role models, mentors and directors in students' daily lives. This research also explores how religious values, such as honesty, discipline and empathy, are integrated into school activities and implemented in students' lives. This character building involves all school components, including collaboration between teachers and active participation of students in various activities that prioritize moral and spiritual values. Apart from that, in the context of character formation, the influence of social media is also a concern, where students are given the understanding to filter and select information that is in accordance with religious teachings and noble values. Thus, character formation based on religious values ​​at the MTS 1 Pandeglang school is expected to produce individuals who are not only academically intelligent, but also have good morals in social life.